2002
DOI: 10.1067/mtc.2002.121971
|View full text |Cite
|
Sign up to set email alerts
|

In vitro engineering of heart muscle: Artificial myocardial tissue

Abstract: Using a clinically well-established collagen matrix, contractile myocardial tissue can be engineered in vitro successfully. Mechanical and biologic properties of artificial myocardial tissue resemble native cardiac tissue. Use of artificial myocardial tissues might be a promising approach to reconstitute degenerated or failing cardiac tissue in many disease states and therefore provide a reasonable alternative to whole organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(64 citation statements)
references
References 8 publications
4
59
0
1
Order By: Relevance
“…25 Crude myocyte cultures were mainly contaminated with fibroblasts, and, to a lower extent, with endothelial and smooth muscle cells. Freshly isolated neonatal rat cardiomyocytes and RAT-1 fibroblasts (NIH RAT-1) were transduced in suspension in a rotation incubator at a MOI of 7 in DMEM with 10% fetal calf serum (Invitrogen, Karlsruhe, Germany), 2 mmol/l L-glutamine (PAA, Linz, Austria), penicillin (PAA, Linz, Austria, 100 U/ml) and streptomycin (PAA, Linz, Austria, 100 mg/ml).…”
Section: Lentiviral Transduction Of Cardiomyocytes and Rat-1 Fibroblamentioning
confidence: 99%
“…25 Crude myocyte cultures were mainly contaminated with fibroblasts, and, to a lower extent, with endothelial and smooth muscle cells. Freshly isolated neonatal rat cardiomyocytes and RAT-1 fibroblasts (NIH RAT-1) were transduced in suspension in a rotation incubator at a MOI of 7 in DMEM with 10% fetal calf serum (Invitrogen, Karlsruhe, Germany), 2 mmol/l L-glutamine (PAA, Linz, Austria), penicillin (PAA, Linz, Austria, 100 U/ml) and streptomycin (PAA, Linz, Austria, 100 mg/ml).…”
Section: Lentiviral Transduction Of Cardiomyocytes and Rat-1 Fibroblamentioning
confidence: 99%
“…Coculturing neonatal cardiomyocytes, fibroblasts and collagen within bioreactors produced constructs that may promise for the repair of larger scar areas of the myocardium (Van Luyn et al 2002). Seeded neonatal rat cardiomyocytes in a collagen matrix demonstrated contractility both spontaneously and in response to electrical and chemical stimulation (Kofidis et al 2002). Further work on the tissue engineering of cardiac muscle suggested that such constructs had superior wall thickness and uniformity of tissue architecture when perfused (Carrier et al 2002a).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Tissue engineering using biological and synthetic matrix is now associated with cell therapy, the goal is to develop a bioartificial myocardium [22][23][24][25][26][27]. The MAGNUM Clinical Trial (Myocardial Assistance by Grafting a New Upgraded bioartificial Myocardium) is under development by our group [28].…”
Section: Cellular Cardiomyoplastymentioning
confidence: 99%